Plan estratégico para la empresa “Andicolor” en la ciudad de Loja - Ontaneda Calva, Martin José (2014)
The purpose of this research is to conduct a Strategic Plan Andi Color Company of the City of Loja. With the overall objective is “To develop a strategic plan for the company" Andi Color” in the city of Loja" arises. First of materials and methods used within the research, we used the inductive method to determine the results of the project, the same that were obtained through the techniques applied, in order to be able to determine the different functions and activities performed by company employees Andi Color Loja, object of study, the deductive method was used to analyze data from general about the Strategic Plan for the company Andi Color and suggest the proposal under consideration, historical method comprises the methodologies, techniques and guidelines to be used by primary sources in research, the description method, which allowed to describe the current situation being experienced by the joint study, the study was able to learn the actual administrative business processes and their actions; With the applied techniques allowed us to implement a customer survey on a sample of 362 surveys, a survey of 10 employees and an interview with the company manager Andi Color , this information helped us to develop the strengths , weaknesses, opportunities and threats, always relying on field research in the design of the SWOT matrix. In the same way an internal and external analysis was performed by applying the EFE and IFE Matrix. According to the analysis of EFI and EFE matrices, it is determined that EFE is the weighted factor of 2, 72, opportunities have a value of 1.97, and the threat of 071, indicating that opportunities prevail over the threats. On the other Party of the weighted factor have a weighting matrix EFI 2.46; Fortresses have a value of 1.57, and a value of 0.89 weaknesses indicating that the strengths prevail over the Weaknesses. With these considerations by High Impact Matrix, four objectives, among which we were raised, optimize enterprise infrastructure Andi Color, implement an advertising plan to position the company to the stock market Andi Color, improve care customer services provided by the company developing standards of care, to propose an organizational structure to improve internal processes, implement these goals have cost $ 10,162 U.S. dollars. Finally it has come to determine Based on interviews, surveys, managers, employees and customers of the company Andi Color, it no has a Strategic Plan, which allows optimizing the product to customers, it is necessary to strengthen them and you implement new strategies to address them. It can be determined that the company must Andi Color increasing the volume of sales of the products offered by 60 % by the year 2015. Color Us Andi must have fair prices on products offered. Employees report that the company Andi Color must implement a plan of advertising media especially radio and print media.